Verticalização de molares inferiores com auxílio de mini-implantes como ancoragem - Monteiro, Renata Furquim Moura (2015)
Objective: The aim of this study was to verify the effectiveness of the molar upright, using an orthodontic mechanic with mini-implants as anchorage and quantify through panoramic radiographs, the angle and vertical changes resulting from the upright. Methods: The experimental sample consisted of 36 panoramic radiographs, 18 initial and 18 final of 18 Brazilians patients of both genders (10 female and 8 male; age range 20-59 years; mean 38,60 years). Among these patients, 2 had bilateral absences totaling 20 teeth subjected to upright. These patients received a cantilever for uprighting the molar, employed until the clinical evaluation of its correct vertical integration and standardization of occlusion. Panoramic radiographs were taken of the patients at the beginning (T1) and end (T2) of treatment. The mean values at T1 were compared with the mean values at T2. The treatment time ranged from 4 to 11 months, (mean = 6,35 months; SD = 1,95). Results: A statistically significant increase was obtained from 2,73mm mesial vertical change variable and 18,95° in angle, while the vertical change central and distal variables no statistically significant changes was found. Conclusion: It can be concluded that there was an effective upright of the molars, without extrusion of the distal and center aspects of the crown, with only the extrusion of the mesial aspect.